Traumatic experiences, acculturation, and psychological distress among Syrian refugees in Turkey: The mediating role of coping strategies. (March 2021) - Kurt, Gulsah; Acar, İbrahim Hakkı and Ilkkursun, Zeynep and Yurtbakan, Taylan and Acar, Busra and Uygun, Ersin and Acarturk, Ceren
Abstract: Turkey hosts the largest number of refugees in the world. So far, many studies investigated the mental health problems among Syrian refugees in Turkey and other hosting countries. However, little attention has been paid to the acculturation process of Syrian refugees in Turkey. A cross-sectional study was conducted with 409 Syrian refugees in Mardin, Turkey. Results showed that traumatic experiences depleted problem-focused, emotion-focused, and maladaptive coping strategies. Emotion-focused coping strategies mediated the relationship between traumatic experiences and maintenance of the heritage culture and adoption of the destination culture. To conclude, our findings underscore the importance of traumatic experiences and emotion-focused coping strategies for integration of Syrian refugees in Turkey. Psychosocial interventions enhancing emotion-focused coping capacities might mitigate the adverse impact of traumatic experiences on integration. We discussed the strengths and limitations of the study considering the current literature.